Preparation method and application of Co (OH) 2 electrode material for electrochemically detecting total phosphorus

The Co(OH)2 electrode material prepared by hydrothermal method and plasma bombardment treatment combined with differential pulse voltammetry solves the complexity, low sensitivity and susceptibility of total phosphorus detection in the prior art, and achieves fast, sensitive and high-precision total phosphorus detection.

CN119534581APending Publication Date: 2025-02-28HUBEI UNIV OF TECH +1
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411762588.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-03
Publication Date
2025-02-28

AI Technical Summary

Technical Problem

The prior art has problems such as complex pretreatment, low sensitivity and susceptibility to interference when detecting the total phosphorus content of water. The traditional electrochemical method has a long detection time, large equipment and requires frequent maintenance.

Method used

The Co(OH)2 electrode material was used as the working electrode, and the β-Co(OH)2 electrode material with high-efficiency intercalation and electrochemical reaction capabilities was prepared by hydrothermal method and plasma bombardment treatment, and total phosphorus detection was performed in combination with differential pulse voltammetry.

Benefits of technology

Fast, sensitive and high-precision detection of total phosphorus is achieved, with a detection time of less than 40 seconds, a linear detection range of 5×10-4~1mmol/L, and a detection limit of 5×10-5mmol/L. The detection performance of the electrodes has almost not decreased after 6 months of storage at room temperature, and has strong anti-interference ability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119534581A_ABST
    Figure CN119534581A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of electrochemistry, in particular to a preparation method and application of a Co (OH) 2 electrode material for electrochemically detecting total phosphorus, and the preparation method comprises the following steps: A, respectively preparing cobalt nitrate and urea into a cobalt nitrate solution and a urea solution, and mixing the cobalt nitrate solution and the urea solution to obtain a mixed solution; b, a metal cobalt rod is put into the mixed solution obtained in the step A for a reaction, then cooling, washing and drying are conducted, then plasma bombardment and impurity removal are conducted, and the Co (OH) 2 electrode material is obtained and is good in stability, good in detection sensitivity and high in anti-interference capacity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of electrochemical technology, and in particular to a preparation method and application of a Co(OH)2 electrode material for electrochemical detection of total phosphorus. Background Art

[0002] Total phosphorus is a key indicator of water pollution. It refers to the amount of phosphorus in various forms in a water sample, converted to orthophosphate after digestion. It is measured in milligrams of phosphorus per liter of water. Phosphorus in water can exist in the form of elemental phosphorus, orthophosphate, condensed phosphate, metaphosphate, and organically bound phosphate.

[0003] Phosphorus in water is a key element required for algae growth. Excessive phosphorus is the main cause of water pollution and odor, eutrophication of lakes and red tides in bays.

[0004] Currently, the national standard for measuring total phosphorus in water relies on ammonium molybdate spectrophotometry. While this method offers high accuracy, it also suffers from complex procedures, long testing times (2-3 hours), safety concerns stemming from the use of chemical reagents (concentrated sulfuric acid, nitric acid, and perchloric acid), potentially hazardous experimental procedures (high-temperature, high-pressure digestion, and heating on a hot plate), and bulky equipment requiring frequent maintenance.

[0005] Traditional electrochemical methods for detecting total phosphorus in water suffer from complex pretreatment, low sensitivity, and susceptibility to interference. Chemical digestion is used to convert different forms of phosphorus in water into detectable orthophosphate. Subsequently, electrochemical testing techniques are used based on electrode materials to quantitatively analyze phosphate concentration. Cobalt electrodes are widely used for electrochemical detection of phosphate due to their unique selectivity and robustness for phosphate. Patent CN116577393A discloses a potentiometric method for determining phosphate using petal-shaped nano-CoOOH as an electrode material. This method is based on the determination of phosphate by a surface reaction between phosphate and a cobalt oxide electrode to produce cobalt phosphate, which causes a change in the electrode potential of the cobalt oxide electrode. This detection method takes a long time, suffers from poor electrode stability, and has low detection sensitivity. The logarithm (log10) of the phosphate concentration is linearly related to the potential. Furthermore, the electrode is susceptible to interference from dissolved oxygen and chloride ions. Summary of the Invention

[0006] In order to solve the above technical problems, an embodiment of the present invention provides a preparation method and application of a Co(OH)2 electrode material for electrochemical detection of total phosphorus.

[0007] To achieve the above objectives, the embodiments of the present invention adopt the following technical solutions:

[0008] In one aspect, the present invention provides a method for preparing a Co(OH)2 electrode material for electrochemical detection of total phosphorus, comprising the following steps:

[0009] A. respectively configuring cobalt nitrate and urea into a cobalt nitrate solution and a urea solution, and mixing them with each other to obtain a mixed solution;

[0010] B. Add a metal cobalt rod to the mixed solution of step A for reaction, followed by cooling, washing, and drying, and then plasma bombardment and impurity removal to obtain Co(OH)2 electrode material.

[0011] In some embodiments, in step A, the concentration of the cobalt nitrate solution is 20 mmol / L to 200 mmol / L, the concentration of the urea solution is 0.02 mol / L to 0.5 mol / L, and the volume ratio of the cobalt nitrate solution to the urea solution when the two are mixed is 1:1 to 1:2.

[0012] In some embodiments, in step B, the diameter of the metal cobalt rod is 2-4 mm.

[0013] In some embodiments, in step B, the reaction temperature is 120-180° C., and the reaction time is 12-24 h.

[0014] In some embodiments, in step B, the plasma bombardment is performed as follows: the product after cooling, washing and drying is placed in a reactive ion etching machine, with argon as the working gas and oxygen as the process gas, and the vacuum is reduced to 2×10 -5 ~1×10 -4 After Pa, the product surface is treated at a power of 80 to 120 W for 5 to 10 minutes.

[0015] In some embodiments, the flow rate of the argon gas is 80-100 mL / min, and the flow rate of the oxygen gas is 5-15 mL / min.

[0016] On the other hand, the present invention also provides a use of the Co(OH)2 electrode material prepared by the above preparation method in detecting total phosphorus.

[0017] Regarding the application of the Co(OH)2 electrode material prepared by the present invention in the detection of total phosphorus, a three-electrode system is composed of the Co(OH)2 electrode material as the working electrode, a saturated calomel electrode as the reference electrode, and a platinum wire as the auxiliary electrode. The total phosphorus detection is completed using the voltammetric scanning of the electrochemical workstation.

[0018] The specific steps are:

[0019] S1, prepare 0.001ppm, 0.01ppm, 0.1ppm, 1ppm, and 10ppm sodium phosphate solutions respectively, with 0.1M KCl as the supporting electrolyte;

[0020] S2. After inserting the three electrodes into the test solution and stabilizing for 15 minutes, start the differential pulse voltammetry (DPV) test. The test parameters are: scanning voltage range: 0~+1V, step potential: 4mV, amplitude: 50mV, frequency: 50Hz;

[0021] S3. Record the oxidation peak current value at a specific potential (e.g., +0.65V and +0.95V). Data processing: Draw a standard curve based on the oxidation peak current values ​​(Ip) measured in phosphate solutions of different concentrations. Use linear regression analysis to obtain the relationship between current and phosphate concentration. Clean the three electrodes and insert them into the test solution. Perform the DPV test again and substituting the oxidation peak current value (Ip) into the standard curve to obtain the phosphate concentration of the test solution, which is the total phosphorus concentration in the water.

[0022] Compared with the prior art, the present invention has at least the following beneficial effects:

[0023] 1. The β-Co(OH)2 electrode material prepared by the present invention has a typical layered structure, such as Figure 1 As shown in the X-ray diffraction spectrum, a derivative peak corresponding to the (001) crystal plane is displayed near 19°. The interplanar spacing is calculated to be 0.465nm, that is, the interlayer spacing of β-Co(OH)2 reaches 0.465nm, which is conducive to the efficient intercalation and electrochemical reaction of phosphate, thereby achieving highly reversible electrochemical redox behavior. The linear relationship between phosphate concentration and current response can be established by differential pulse voltammetry (DPV). When the differential pulse voltammetry scans the voltage, the reaction process of the electrode is: adsorption of phosphate: the external voltage applied to the electrode promotes the adsorption of phosphate (such as HPO4 2- ) is adsorbed into the interlayer of β-Co(OH)2. Oxidation reaction: As the voltage increases, due to the adsorption of phosphate, phosphate accelerates the transfer of hydroxyl protons in β-Co(OH)2 and combines with it to form H2PO4 - ions, thereby promoting the divalent Co in β-Co(OH)2 2+ Oxidized to trivalent Co 3+ , causing it to change into CoOOH. Further oxidation: When the applied voltage is further increased, CoOOH can continue to be oxidized to CoO2, and this process is also promoted by phosphate. Reduction process: During the reduction process, CoO2 and CoOOH are reduced back to the initial state of the layered structure Co(OH)2. During the entire voltage scan process, the β-Co(OH)2 redox reaction is highly reversible, the reaction current response is highly sensitive, and the current response size is linearly related to the phosphate concentration. It can detect phosphate at a low concentration of 0.00232 mg / L, and the single detection time is less than 40 seconds.

[0024] 2. The linear detection range of the electrochemical voltammetry detection of the Co(OH)2 electrode material of the present invention is 5×10 -4 ~1mmol / L, detection limit is 5×10 -5 mmol / L (i.e. 0.00232 mg / L), which is one order of magnitude lower than the lowest detection limit of ordinary Co(OH)2 electrode without plasma bombardment.

[0025] 3. After six months of storage at room temperature, the detection performance of the Co(OH)2 electrode material of the present invention remained virtually unchanged, demonstrating excellent long-term stability. After 1,000 cyclic voltammetry tests, the current response of the electrode remained stable, with a relative standard deviation of less than 9%.

[0026] 4. The Co(OH)2 electrode material of the present invention has strong anti-interference ability and can - 、NO3 - 、SO4 2- and HCO3 - ) water samples with stable detection performance and a relative error of less than 4.6%, which is significantly better than traditional electrode materials. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 is the X-ray diffraction spectrum of the Co(OH)2 electrode material in Example 1;

[0028] Figure 2 This is the surface SEM image of the Co(OH)2 electrode material in Example 2;

[0029] Figure 3 The standard curve of the response of the Co(OH)2 electrode material in Example 3 to phosphate at concentrations of 0.00232 mg / L to 50 mg / L is shown;

[0030] Figure 4 The standard curve of the response of the Co(OH)2 electrode material in Example 3 to phosphate during 6 months of long-term use;

[0031] Figure 5 Graph showing the test results of the Co(OH)2 electrode material in Example 4 over 1000 cycles;

[0032] Figure 6 The Co(OH)2 electrode material in Example 5 is subjected to the common interfering ions (Cl - 、NO3 - 、SO4 2- and HCO3 - ) The oxidation peak current value in a 5 mg / L phosphate solution with a concentration five times higher;

[0033] Figure 7This is the SEM image of the surface of Co(OH)2 electrode material without plasma treatment;

[0034] Figure 8 The response standard curve of the Co(OH)2 electrode material to phosphate in Example 6;

[0035] Figure 9 This is the standard curve of the response of Co(OH)2 electrode material to phosphate without plasma treatment. DETAILED DESCRIPTION

[0036] The following will be combined with the accompanying drawings to clearly and completely describe the technical solutions in some embodiments of the present disclosure. Obviously, the embodiments described are only some embodiments of the present disclosure, not all embodiments. Based on the embodiments provided by the present disclosure, all other embodiments obtained by ordinary technicians in this field are within the scope of protection of the present disclosure.

[0037] Example 1

[0038] Prepare 30mL of 40mmol / L cobalt nitrate solution and 40mL of 0.1mol / L urea solution respectively. After the cobalt nitrate solution and urea solution are evenly mixed, transfer the mixed solution to a hydrothermal reactor, ensuring that the liquid volume in the reactor does not exceed 80% of its maximum capacity. At the same time, place a metal cobalt rod with a diameter of 2mm in the hydrothermal reactor. After the hydrothermal reactor is sealed, place it in an oven and react at 150℃ for 18 hours. Cool, wash and dry. Then, place the cobalt electrode with cobalt hydroxide deposited on the surface in a reactive ion etcher with argon as the working gas and oxygen as the process gas. When the vacuum degree drops to 5×10 -5 After Pa, the surface of the cobalt oxide electrode was treated at a power of 120W for 5 minutes. The argon flow rate was maintained at 100 ml / min, and the oxygen flow rate was controlled at 5 ml / min, and then was extracted from the reaction chamber to eliminate surface impurities. After the treatment, the Co(OH)2 electrode material was obtained. Figure 1 As shown, the Co(OH)2 electrode material is a β-Co(OH)2 crystal form, and a characteristic diffraction peak of the (001) crystal plane appears near 19°.

[0039] Example 2

[0040] Prepare 20mL of 50mmol / L cobalt nitrate solution and 30mL of 0.1mol / L urea solution respectively. After the cobalt nitrate solution and urea solution are evenly mixed, transfer the mixed solution to a hydrothermal reactor, ensuring that the liquid volume in the reactor does not exceed 80% of its maximum capacity. At the same time, place a metal cobalt rod with a diameter of 2mm in the hydrothermal reactor. After the hydrothermal reactor is sealed, place it in an oven and react at 120℃ for 24 hours. Cool, wash and dry. Then, place the cobalt electrode with cobalt hydroxide deposited on the surface in a reactive ion etcher with argon as the working gas and oxygen as the process gas. When the vacuum degree drops to 4×10 -5 After Pa, the surface of the cobalt oxide electrode was treated at a power of 120W for 8 minutes. The argon flow rate was maintained at 100 ml / min, and the oxygen flow rate was controlled at 5 ml / min, and then was extracted from the reaction chamber to eliminate surface impurities. After the treatment, the Co(OH)2 electrode material was obtained. Figure 2 As shown, the Co(OH)2 electrode material has a clear and obvious layered structure and no impurities on the surface.

[0041] Example 3

[0042] Prepare 20mL of 50mmol / L cobalt nitrate solution and 30mL of 0.1mol / L urea solution respectively. After the cobalt nitrate solution and urea solution are evenly mixed, transfer the mixed solution to a hydrothermal reactor, ensuring that the liquid volume in the reactor does not exceed 80% of its maximum capacity. At the same time, place a metal cobalt rod with a diameter of 2mm in the hydrothermal reactor. After the hydrothermal reactor is sealed, place it in an oven and react at 120℃ for 24 hours. Cool, wash and dry. Then, place the cobalt electrode with cobalt hydroxide deposited on the surface in a reactive ion etcher with argon as the working gas and oxygen as the process gas. When the vacuum degree drops to 4×10 -5 After 1 Pa, the cobalt oxide electrode surface was treated at 120 W for 8 minutes. The argon flow rate was maintained at 100 ml / min, and the oxygen flow rate was controlled at 5 ml / min. The argon flow was then evacuated from the reaction chamber to remove surface impurities. After the treatment, the Co(OH)2 electrode material was obtained.

[0043] Phosphate determination: The Co(OH)2 electrode material prepared in Example 3 was used as the working electrode, the saturated calomel electrode was used as the reference electrode, and the platinum wire was used as the auxiliary electrode to form a three-electrode system. Sodium phosphate solutions of different concentrations (0.001ppm to 50ppm) were prepared, and the supporting electrolyte was 0.1M KCl. After the three electrodes were inserted into the liquid to be tested, the differential pulse voltammetry test was started with a scanning voltage range of 0 to +1V, a step potential of 4mV, an amplitude of 50mV, and a frequency of 50Hz. The oxidation peak current value at a specific potential (such as +0.65V and +0.95V) was recorded, as shown in FIG. Figure 3As shown in the figure, there is a good linear relationship between the peak current and the phosphate concentration. The slope of the phosphate standard curve after linear regression is 1.1505μA / (mg / L). At the same time, the electrode was stored for 6 months, and the phosphate standard curve was checked every month during the storage period. Figure 4 As shown, the results show that the slope of the electrode standard curve has basically not changed, indicating that the electrode is stable and has a long shelf life.

[0044] Example 4

[0045] Prepare 50mL of 200mmol / L cobalt nitrate solution and 50mL of 0.2mol / L urea solution respectively. After the cobalt nitrate solution and urea solution are evenly mixed, transfer the mixed solution to a hydrothermal reactor, ensuring that the liquid volume in the reactor does not exceed 80% of its maximum capacity. At the same time, place a metal cobalt rod with a diameter of 2mm in the hydrothermal reactor. After the hydrothermal reactor is sealed, place it in an oven and react at 180℃ for 12 hours. Cool, wash and dry. Then, place the cobalt electrode with cobalt hydroxide deposited on the surface in a reactive ion etcher with argon as the working gas and oxygen as the process gas. When the vacuum degree drops to 6×10 -5 After 1 Pa, the cobalt oxide electrode surface was treated at 80W for 5 minutes. The argon flow rate was maintained at 100 ml / min, and the oxygen flow rate was controlled at 10 ml / min. The argon flow was then evacuated from the reaction chamber to remove surface impurities. After the treatment, the Co(OH)2 electrode material was obtained.

[0046] Electrode stability test: The Co(OH)2 electrode material prepared in Example 4 was used as the working electrode, a saturated calomel electrode was used as the reference electrode, and a platinum wire was used as the auxiliary electrode to form a three-electrode system. A 5ppm sodium phosphate solution was prepared, and the supporting electrolyte was 0.1M KCl. After the three electrodes were inserted into the test solution, a cyclic voltammetry test was performed with a scanning voltage range of 0 to +1V and a scanning rate of 50mV / s. The cyclic current-time curve and the oxidation peak current value at +0.95V were recorded. Figure 5 In 1000 cycles of cyclic voltammetry, the relative standard deviation of the peak current was less than 9%, indicating good stability of the electrode.

[0047] Example 5

[0048] Prepare 20mL of 50mmol / L cobalt nitrate solution and 20mL of 0.05mol / L urea solution respectively. After the cobalt nitrate solution and urea solution are evenly mixed, the mixed solution is transferred to a hydrothermal reactor, ensuring that the liquid volume in the reactor does not exceed 80% of its maximum capacity. At the same time, a metal cobalt rod with a diameter of 2mm is placed in the hydrothermal reactor. After the hydrothermal reactor is sealed, it is placed in an oven and reacted at 160°C for 12 hours, cooled, washed and dried. Subsequently, the cobalt electrode with cobalt hydroxide deposited on the surface is placed in a reactive ion etcher, with argon as the working gas and oxygen as the process gas. When the vacuum degree drops to 8×10 -5 After Pa, the surface of the cobalt oxide electrode was treated for 10 minutes at a power of 100 W. The argon flow rate was maintained at 90 ml / min and the oxygen flow rate was controlled at 10 ml / min, and then they were evacuated from the reaction chamber to eliminate surface impurities. After the treatment, the Co(OH)2 electrode material was obtained.

[0049] Electrode anti-interference performance test: The Co(OH)2 electrode material prepared in Example 5 was used as the working electrode, the saturated calomel electrode was used as the reference electrode, and the platinum wire was used as the auxiliary electrode to form a three-electrode system. Five sodium phosphate solutions with a concentration of 5ppm were prepared, and 25ppm of Cl was added to each of the four solutions. - 、NO3 - 、SO4 2- and HCO3 2- The supporting electrolyte is 0.1M KCl. After inserting the three electrodes into the test solution, differential pulse voltammetry was performed. The scanning voltage range was 0 to +1V, the step potential was 4mV, the amplitude was 50mV, and the frequency was 50Hz. The oxidation peak current value at a specific potential (+0.95V) was recorded. The results are as follows: Figure 6 As shown. - 、NO3 - 、SO4 2- and HCO3 2- The addition of has almost no effect on the electrode response current, indicating that the electrode has strong anti-interference ability.

[0050] Example 6

[0051] Prepare 30mL of 40mmol / L cobalt nitrate solution and 30mL of 0.02mol / L urea solution respectively. After the cobalt nitrate solution and urea solution are evenly mixed, transfer the mixed solution to a hydrothermal reactor, ensuring that the liquid volume in the reactor does not exceed 80% of its maximum capacity. At the same time, place a metal cobalt rod with a diameter of 2mm in the hydrothermal reactor. After the hydrothermal reactor is sealed, place it in an oven and react at 180℃ for 12 hours. Cool, wash and dry. Then, place the cobalt electrode with cobalt hydroxide deposited on the surface in a reactive ion etcher with argon as the working gas and oxygen as the process gas. When the vacuum degree drops to 8×10-5 After Pa, the surface of the cobalt oxide electrode was treated for 10 minutes at a power of 100 W. The argon flow rate was maintained at 100 ml / min and the oxygen flow rate was controlled at 10 ml / min, and then they were evacuated from the reaction chamber to eliminate surface impurities. After the treatment, the Co(OH)2 electrode material was obtained.

[0052] Test example: Application of Co(OH)2 electrode material in total phosphorus detection

[0053] Water sample pretreatment:

[0054] The samples were treated with commercial digestion equipment (TDR-30S multifunctional intelligent digester from Shenzhen Tongao Technology Co., Ltd.) to oxidize the phosphorus in the water into phosphate.

[0055] Electrochemical detection:

[0056] Test group: Co(OH)2 electrode material prepared in Example 6 was used as the working electrode, a saturated calomel electrode was used as the reference electrode, and a platinum wire was used as the auxiliary electrode to form a three-electrode system. The electrodes were placed in 50mL of a standard sample of total phosphorus of different concentrations. The supporting electrolyte was 0.1M KCl. The distance between the working electrode and the auxiliary electrode was 1cm. Differential pulse voltammetry was performed using the following test parameters: a sweep voltage range of 0 to +1V, a step potential of 4mV, an amplitude of 50mV, and a frequency of 50Hz. The oxidation peak current value of the differential pulse voltammetry curve at +0.95V was recorded. The current value at this voltage was used to create a standard curve for the total phosphorus concentration. The total phosphorus value was obtained by substituting the water sample detection current value into the standard curve.

[0057] The control group is different from the experimental group in that its electrode material has not been treated with plasma (i.e., the following process is not used): the cobalt electrode with cobalt hydroxide deposited on the surface is placed in a reactive ion etching machine with argon as the working gas and oxygen as the process gas. When the vacuum degree is reduced to 8×10 -5 After 10 Pa, the cobalt oxide electrode was surface treated at 100 W for 10 minutes. The argon flow rate was maintained at 100 ml / min, and the oxygen flow rate was controlled at 10 ml / min. It was then evacuated from the reaction chamber to remove surface impurities and used directly as a working electrode. All other conditions remained unchanged.

[0058] pass Figure 7 The Co(OH)2 electrode material on the electrode that has not been plasma treated has a layered structure, but there are a lot of impurities on its surface.

[0059] pass Figure 8 and Figure 9From the standard curves of the Co(OH)2 electrode material and the Co(OH)2 electrode material without plasma treatment, it can be seen that the response slope of the Co(OH)2 electrode material to total phosphorus is much higher than that of the Co(OH)2 electrode material without plasma treatment, which has good sensitivity and is more conducive to the detection of total phosphorus.

[0060] The above test group method and the national standard method were used to detect standard water samples with known total phosphorus concentrations. The results can be seen from Table 1 below. The results of this test group method are closer to the total phosphorus concentration in the standard water samples, with a maximum error of 4%, indicating that the Co(OH)2 electrode material has a smaller error and higher accuracy in detecting total phosphorus in actual water samples.

[0061] Table 1 Comparison of phosphate concentration in standard water samples detected by the test group method and the national standard method

[0062]

[0063] Example 7

[0064] Prepare 60mL of 200mmol / L cobalt nitrate solution and 60mL of 0.5mol / L urea solution respectively. After the cobalt nitrate solution and urea solution are evenly mixed, transfer the mixed solution to a hydrothermal reactor, ensuring that the liquid volume in the reactor does not exceed 80% of its maximum capacity. At the same time, place a metal cobalt rod with a diameter of 4mm in the hydrothermal reactor. After the hydrothermal reactor is sealed, place it in an oven and react at 180℃ for 24 hours. Cool, wash and dry. Then, place the cobalt electrode with cobalt hydroxide deposited on the surface in a reactive ion etcher with argon as the working gas and oxygen as the process gas. When the vacuum degree drops to 2×10 -5 After Pa, the surface of the cobalt oxide electrode was treated for 10 minutes at a power of 120 W. The argon flow rate was maintained at 100 ml / min and the oxygen flow rate was controlled at 15 ml / min, and then they were evacuated from the reaction chamber to eliminate surface impurities. After the treatment, the Co(OH)2 electrode material was obtained.

[0065] Example 8

[0066] Prepare 30mL of 20mmol / L cobalt nitrate solution and 30mL of 0.02mol / L urea solution respectively. After the cobalt nitrate solution and urea solution are evenly mixed, transfer the mixed solution to a hydrothermal reactor, ensuring that the liquid volume in the reactor does not exceed 80% of its maximum capacity. At the same time, place a metal cobalt rod with a diameter of 3mm in the hydrothermal reactor. After the hydrothermal reactor is sealed, place it in an oven and react at 120℃ for 12 hours. Cool, wash and dry. Then, place the cobalt electrode with cobalt hydroxide deposited on the surface in a reactive ion etcher with argon as the working gas and oxygen as the process gas. When the vacuum degree drops to 6×10 -5After Pa, the surface of the cobalt oxide electrode was treated for 10 minutes at a power of 110 W. The argon flow rate was maintained at 90 ml / min and the oxygen flow rate was controlled at 5 ml / min, and then they were evacuated from the reaction chamber to eliminate surface impurities. After the treatment, the Co(OH)2 electrode material was obtained.

[0067] In the description of this specification, specific features, structures, materials or characteristics may be combined in an appropriate manner in any one or more embodiments or examples.

[0068] The above description is merely a specific embodiment of the present invention, but the scope of protection of the present invention is not limited thereto. Any modifications or substitutions that can be easily conceived by a person skilled in the art within the technical scope disclosed in the present invention should be included in the scope of protection of the present invention. Therefore, the scope of protection of the present invention should be based on the scope of protection of the claims.

Claims

1. A method for preparing a Co(OH)2 electrode material for electrochemical detection of total phosphorus, characterized in that: The following steps are involved: A. respectively configuring cobalt nitrate and urea into a cobalt nitrate solution and a urea solution, and mixing them with each other to obtain a mixed solution; B. Put a metal cobalt rod into the mixed solution of step A for reaction, then cool, wash and dry, and then plasma bombard and remove impurities to obtain Co(OH)2 electrode material.

2. The preparation method according to claim 1, characterized in that: In step A, the concentration of the cobalt nitrate solution is 20 mmol / L to 200 mmol / L, the concentration of the urea solution is 0.02 mol / L to 0.5 mol / L, and when the two are mixed, the volume ratio of the cobalt nitrate solution to the urea solution is 1:1 to 1:

2.

3. The preparation method according to claim 1, characterized in that: In step B, the diameter of the metal cobalt rod is 2-4 mm.

4. The preparation method according to claim 1, characterized in that: In step B, the reaction temperature is 120-180° C., and the reaction time is 12-24 hours.

5. The preparation method according to claim 1, characterized in that: In step B, the plasma bombardment is performed by the following steps: the product after cooling, washing and drying is placed in a reactive ion etcher, with argon as the working gas and oxygen as the process gas, and the vacuum is reduced to 2×10 -5 ~1×10 -4 After Pa, the product surface is treated at a power of 80 to 120 W for 5 to 10 minutes.

6. The preparation method according to claim 5, characterized in that: The flow rate of the argon gas is 80-100 mL / min, and the flow rate of the oxygen gas is 5-15 mL / min.

7. Use of the Co(OH)2 electrode material prepared by the preparation method as claimed in claims 1 to 6 in detecting total phosphorus.

Citation Information

Patent Citations

  • Petal-shaped nano CoOOH material phosphate electrode as well as preparation method and application thereof

    CN116577393A